Introduction to the special section: innovative perspectives on systems of sustainable consumption and production. Issue 1 (1st January 2019) - Cohen, Maurie J.
Abstract: This introductory article to the special section first provides a cursory overview of the history of sustainable consumption and production as a policy issue dating back to the Rio Earth Summit in 1992. While sustainable production has been absorbed over the past three decades into prevailing societal commitments, governance structures, and business models, the companion notion of sustainable consumption has struggled to garner equal attention. The article then reviews the delimited framing that has been adopted to ameliorate the social and environmental effects of contemporary systems of provision. This conception has involved emphasis on consumer education, information dissemination, and behavioral nudging. These "weak" modes are deemed inadequate and need to be supplanted by initiatives that catalyze processes of system innovation as part of efforts to facilitate sustainability transitions of underlying socio-technical systems of consumption and production. This article also provides brief overviews of the four contributions that comprise this special section.